INCLUSIVE EDUCATION: A CASE STUDY ABOUT TEACHER'S WORK IN EARLY CHILDHOOD EDUCATION - Batista, Bruna Rafaela de [UNESP]; Manzoli, Luci Pastor [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
The inclusive education is supported by the Brazilian legislation ensuring educational access for all students. In this sense, it becomes required to observe from the beginning, with the early childhood education, what are the educational actions that are being carried out to guarantee the right of students PAEE. Thus, this study case aimed to verify how the pedagogical work works with students PAEE in a common an early childhood education classroom. A from the regular school system of early childhood education participated of the study. Data collection occurred in a school in a city in the state of Sao Paulo. To achieve the proposed objective, the participant answered a half-structured question set through interview technique that addressed identification data and four themes, namely: Information about the student PAEE; Teaching work; School and Family and Inclusive Education. Qualitative analysis by themes with data obtained through interviews were conducted. As a result, there was the realization of a pedagogic work aimed to include her student as well as the need for greater collaboration among school professionals, and greater participation by the family.
Keywords: Inclusive education; Early childhood education; Pedagogical practice